Assessing the threat of the polyphagous shot hole borer ambrosia beetle and its fungal symbiont – Fusarium euwallaceae, to Persea americana, in South Africa - Van den Berg, Noelani (University of Pretoria, 2024)
Dissertation (MSc (Microbiology))--University of Pretoria, 2019.